12x+11=6x+4

Simple and best practice solution for 12x+11=6x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+11=6x+4 equation:


Simplifying
12x + 11 = 6x + 4

Reorder the terms:
11 + 12x = 6x + 4

Reorder the terms:
11 + 12x = 4 + 6x

Solving
11 + 12x = 4 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
11 + 12x + -6x = 4 + 6x + -6x

Combine like terms: 12x + -6x = 6x
11 + 6x = 4 + 6x + -6x

Combine like terms: 6x + -6x = 0
11 + 6x = 4 + 0
11 + 6x = 4

Add '-11' to each side of the equation.
11 + -11 + 6x = 4 + -11

Combine like terms: 11 + -11 = 0
0 + 6x = 4 + -11
6x = 4 + -11

Combine like terms: 4 + -11 = -7
6x = -7

Divide each side by '6'.
x = -1.166666667

Simplifying
x = -1.166666667

See similar equations:

| 2y^2-12y=54 | | 12x-7y=-49 | | 3x^2=180-21x | | 3x^2-2(11-8)x^2=36x | | 15-12/3 | | (5x-3)=180 | | z^2=81+9y | | 2y+17=180 | | 3n-2=3n-10 | | 2y+7=180 | | 11n^2=-99 | | x^2=12y+144 | | 2x^3-4x^2-2x+1=0 | | 360=x+0.02*x | | 3(4x+6)=9x+112 | | 3a^2-30a=-48 | | 7(h-1)=56 | | ln(3x)dx= | | 3(3-3x)+4=5(x+2) | | 20+21x+x^2=120 | | -5n+1-6n+n-4=10 | | 2x-8/2=14 | | 3p^2+30p+48= | | x^2=11x-21 | | 8x^2+83x+240=0 | | 2x^2-16x+20=0 | | 3x=270/15 | | 2r^2-14r=88 | | 300=x+0.02*x | | 2x^2-4x=o | | 3z^3+6z^2= | | 1/2-1/6x=1/6 |

Equations solver categories